Iowa Birdline update, January 21, 1991 notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Notes for the Iowa Birdline update for January 21, 1991. Highlights include multiple Snowy Owl reports. Epson - sheet feed/flatbed